The perception of the parents toward the online teaching and learning during the covid-19 pandemic - Gyeltshen, Tempa (International Journal of Humanities and Education Development (IJHED), 2022)
On March 5, 2020, the first positive case of COVID-19 was confirmed in Bhutan, and on March 18, all the nationwide schools were closed to decrease the spread of Coronavirus. Like many other countries, Bhutan initiated online teaching and learning to replace traditional face-to-classes during the COVID-19 pandemic to continue children's learning. Lessons were broadcast on television and self-learning materials were distributed to rural schools and those who don't have access to online learning. This study is projected to investigate the parents' perspectives on online teaching and Learning during the COVID-19 pandemic. This study was conducted in a small village under Shumar Gewog (block) under Pema Gatshel Dzongkhag (district) in the East of Bhutan. This paper was a qualitative study based on in-depth semi-structured interviews which were limited to thirty key informants due to several limitations. Data were analyzed with a content analysis approach. The study found that there is a mixed perception towards online teaching and learning during the COVID-19 pandemic. The result suggested that online classes during the COVID-19 pandemic will assist their children to keep engaged, it helps many students to clear doubts and understand the concepts in better ways, it helps the students to use Information and Communication Technology (ICT) which enhances their capability to explore the world beyond. On the other hand, it is connected with the parents concerning the quality of education due to the online classes, the poor network connectivity issues, wastage of money on data, and most of the children are engaged in online games and other unhealthy websites which can result in the risk of cyberbullying.